The Adoption of Open Educational Resources by One Community College Math Department - Hilton III, John Levi; Gaudet, Donna; Clark, Phil; Robinson, Jared; Wiley, David (International Review of Research in Open and Distributed Learning, 2013)
The high cost of textbooks is of concern not only to college students but also to society as a whole. Open textbooks promise the same educational benefits as traditional textbooks; however, their efficacy remains largely untested. We report on one community college’s adoption of a collection of open resources across five different mathematics classes. During the 2012 fall semester, 2,043 students in five different courses used these open access resources. We present a comparison between the previous two years in terms of the number of students who withdrew from the courses and the number that completed the courses with a C grade or better. Our analysis suggests that while there was likely no change in these educational outcomes, students who have access to open access materials collectively saved a significant amount of money. Students and faculty were surveyed as to their perceptions of these materials and the results were generally favorable.